2022
DOI: 10.1155/2022/9217268
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Mangostin-Loaded Transferrin-Conjugated Lipid-Polymer Hybrid Nanoparticles: Development and Characterization for Tumor-Targeted Delivery

Abstract: Alpha-mangostin, a natural xanthone mainly extracted from the pericarp of Garcinia mangostana, has been shown to have promising anticancer properties in many types of cancer. However, the therapeutic potential of α-mangostin has been limited so far due to its poor aqueous solubility and low oral bioavailability, which limited its biopharmaceutical applications. Furthermore, α-mangostin failed to specifically reach tumors at a therapeutic concentration due and rapid elimination in vivo. We hypothesized that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(58 reference statements)
0
5
0
Order By: Relevance
“… 28 Sakpakdeejaroen and colleagues reported enhanced cellular accumulation when α-mangostin was entrapped in transferrin-conjugated lipid polymer hybrid nanoparticles and found to be effective in antiproliferative activity of various cancer cell lines. 29 Therefore, transferrin-conjugated lipid polymer hybrid nanoparticle is a highly promising therapeutic system that should be further optimized as therapeutic tools for cancer treatment. 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 Sakpakdeejaroen and colleagues reported enhanced cellular accumulation when α-mangostin was entrapped in transferrin-conjugated lipid polymer hybrid nanoparticles and found to be effective in antiproliferative activity of various cancer cell lines. 29 Therefore, transferrin-conjugated lipid polymer hybrid nanoparticle is a highly promising therapeutic system that should be further optimized as therapeutic tools for cancer treatment. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 29 Therefore, transferrin-conjugated lipid polymer hybrid nanoparticle is a highly promising therapeutic system that should be further optimized as therapeutic tools for cancer treatment. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, homotypic targeting is based upon the interaction among those adhesion proteins, which are present on the surface of cancer cells, and that can be used to coat the surface of nanoemulsion droplets [ 15 ]. Transferrin (TRF) has been frequently employed as the ligand for active targeting [ 16 , 17 , 18 ], since it shows a relatively high interspecies equivalence with respect to receptor binding [ 19 ] and its receptor is over-expressed in melanoma [ 16 ]. Literature evidence shows that nanoemulsions can be successfully conjugated to proteins by using maleimide-based linkers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomicelle formation and polymeric nanoparticle encapsulation have been proven to enhance the solubility of AM and facilitate its targeted delivery to specific organs [18]. Various studies, conducted both in vitro and in vivo, have demonstrated the enhanced cytotoxicity, antiproliferative activity, and induction of apoptosis when AM is delivered through these nanoparticle systems, such as transferrin-conjugated lipid-polymer hybrid NPs [19], AM-encapsulated poly(lactic-co-glycolic) acid (PLGA) NPs [20], AM-CS/sodium alginate NPs [21], AM-CS/carrageenan NPs [22] and hyaluronic acid-coated CS-NPs [23]. Additionally, NPs constructed with crosslinked CS and glyoxal have demonstrated controlled-release properties, making them a promising drug-delivery system for hydrophobic compounds such as AM [24].…”
Section: Introductionmentioning
confidence: 99%